Control of Variable Speed Variable Pitch Wind Turbine at Above and Below Rated Wind Speed. (22nd October 2014) - Rajendran, Saravanakumar; Jena, Debashisha
Abstract : The paper presents a nonlinear approach to wind turbine (WT) using two-mass model. The main aim of the controller in the WT is to maximize the energy output at varying wind speed. In this work, a combination of linear and nonlinear controllers is adapted to variable speed variable pitch wind turbines (VSVPWT) system. The major operating regions of the WT are below (region 2) and above rated (region 3) wind speed. In these regions, generator torque control (region 2) and pitch control (region 3) are used. The controllers in WT are tested for below and above rated wind speed for step and vertical wind speed profile. The performances of the controllers are analyzed with nonlinear FAST (Fatigue, Aerodynamics, Structures, and Turbulence) WT dynamic simulation. In this paper, two nonlinear controllers, that is, sliding mode control (SMC) and integral sliding mode control (ISMC), have been applied for region 2, whereas for pitch control in region 3 conventional PI control is used. In ISMC, the sliding manifold makes use of an integral action to show effective qualities of control in terms of the control level reduction and sliding mode switching control minimization.